Women living with HIV/AIDS: sleep impairment, anxiety and depression symptoms Mulheres portadoras de HIV/AIDS: características do sono, sintomas de ansiedade e depressão - Priscila Junqueira; Silvia Bellucci; Sueli Rossini; Rubens Reimão (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate sleep impairment, symptoms of anxiety and depression, and associations with sleep characteristics of sleep in female HIV/AIDS patients. METHOD: 30 female patients with HIV/AIDS were evaluated along with 30 female controls with a mean age of 35.4 years in the study group and 33.1 years in the control group, with: a) the Pittsburgh Sleep Quality Index; b) the Beck Anxiety Inventory; c) the Beck Depression Inventory. RESULTS: Sleep quality was more impaired in AIDS patients than in those with HIV+ or in controls. The AIDS patients showed more symptoms of anxiety. There were associations of sleep impairment with anxiety in HIV+ patients; whereas in AIDS patients associations were found between sleep impairment and depression. CONCLUSION: There was sleep quality in the presence of symptoms of anxiety and depression. In HIV+ patients, sleep impairment was associated with anxiety, while in AIDS patients sleep impairment was associated with depression. OBJETIVO: Avaliar o sono, verificar sintomas de ansiedade e depressão e associações com as características do sono de mulheres portadoras de HIV/AIDS. MÉTODO: Foram avaliadas 30 mulheres portadoras de HIV/AIDS e 30 controles com média de idade para o grupo estudo de 33,1 anos (p=0,320), utilizando-se os seguintes instrumentos: a) Índice de Qualidade do Sono de Pittsburgh; b) Inventário de Ansiedade Beck; c) Inventário de Depressão Beck. RESULTADOS: Verificou-se que a qualidade do sono estava mais prejudicada nas doentes de AIDS em comparação com as soropositivas e o grupo controle. As doentes de AIDS apresentaram mais sintomas de ansiedade. Ocorreram associações do comprometimento do sono com sintomas de ansiedade nas mulheres soropositivas; e nas doentes de AIDS associações foram verificadas do sono e sintomas de depressão. CONCLUSÃO: Houve prejuízo na qualidade do sono, associada a presença de sintomas de ansiedade e depressão. Nas mulheres soropositivas o comprometimento do sono associou-se com a ansiedade e nas doentes de AIDS sono associou-se com a depressão.